2013
DOI: 10.1111/ped.12066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of black stain and associated risk factors in preschool Spanish children

Abstract: The regular consumption of foods rich in iron and the use of iron supplements during pregnancy and early childhood, could favor the development of chromogenic microbiota. The prevalence of black stain did not differ significantly between non-emigrant and immigrant children in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 16 publications
2
37
0
2
Order By: Relevance
“…BS is a common finding in children; however it can be also seen in adults [3]. Studies have shown equal prevalence in both sexes [4, 5]. The characterization of factors contributing to the formation of BS and its nature has become of interest since association between the presence of BS and lower caries experience in children was noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BS is a common finding in children; however it can be also seen in adults [3]. Studies have shown equal prevalence in both sexes [4, 5]. The characterization of factors contributing to the formation of BS and its nature has become of interest since association between the presence of BS and lower caries experience in children was noted.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear how the presence of BS on the tooth surface reduces susceptibility to caries. The dominant occurrence on smooth surfaces was not associated with lower caries experience on these surfaces which implies that caries resistance in children with BS is a result of a general lower caries activity rather than a localized effect [4, 5, 9, 14–19]. …”
Section: Introductionmentioning
confidence: 99%
“…A population study in a birth cohort showed that when the researchers controlled for potential confounding and mediator factors, the presence of BS could have a protective effect for the occurrence of dental caries in primary dentition (age 5) 14 . In contrast, other studies have not revealed such protective effects 15,16 . It is important to point out that these studies have not controlled for potential risk indicators that could be associated with either black stains or dental caries.…”
Section: Introductionmentioning
confidence: 40%
“…Another hypothesis is related to a probable higher content of total calcium and inorganic phosphates in the group of children with black spots 21 , which could reduce the caries occurrence by reducing the dissolution of enamel, allowing the maintenance of a more stable pH, and providing higher buffer capacity of saliva 22 . The regular consumption of iron-rich foods or iron supplements during early childhood could be reasons for favoring chromogenic microbiota development 16 . Lactoferrin, a major iron-binding protein constituent of milk and cheese, has antibacterial activity against S. mutans, preventing dental caries development 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ferric sulfi de can be formed by the reaction between hydrogen sulfi de produced by bacterial action and iron in the saliva or gingival sulcus fl uid. In one study, a group of 6-year-old Spanish children with black stain had consumed a signifi cantly higher proportion of iron supplements than children without black stains 8 . Chromogenic bacteria are also an etiologic factor in the production of black pigment.…”
Section: Introductionmentioning
confidence: 99%